DINAMIKA UNSUR FOSFOR PADA TIAP HORISON PROFIL TANAH MASAM - Dewi Firnia (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
Phosphorus is a macro essential nutrient for plants that are needed in large quantities third after Nitrogen and Potassium. Phosphorus acts as an activator of various plant metabolism enzymes and is a component of chlorophyll. Phosphorus is a necessary element in large amounts (macro nutrients), the amount of phosphorus in plants is smaller than nitrogen and potassium, but phosphorus is the key to plant life by absorbing phosphorus in the form of primary orthophosphate ions (H2PO4-) and secondary orthophosphate ions (HPO42-). In acid soils, the phosphate will be compounded in Al-P and Fe-P forms, whereas in alkaline soil, phosphate will be compounded with calcium as Ca-P forming a soluble complex compound. This research was conducted with the aim of evaluating the relationship and interrelations between the dynamics of phosphorus nutrients to some soil chemical properties on each acid soil profile horizon. This research was conducted in Laboratory of Soil Chemistry and Fertility Department of Soil Science and Land Resources Faculty of Agriculture, IPB. The soil samples used in this research were soil samples originating from the location of Neglasari Jasinga Bogor Village and Padasuka Village Maja Lebak District of Banten Province was taken per horison in soil profile. The results of the two land sites used showed that the dynamics of the availability of phosphorus nutrients. This dynamic was due to the presence of soil pH and aluminum solubility within each soil horizon. On the land profile of origin of Jasinga and lebak that the value of Al-dd would be high if the low soil pH value and available P value would be high if there was a decrease in soil pH value and the value of Al-dd soil.Keywords: acid soil, aluminum, phosphorus